The Effectiveness of Using Mnemonics Strategy to the Students' Vocabulary Mastery at the Eighth Grade - Verawati, Kezia; Aruan, Rumiri; Masyhur, Masyhur (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This pre-experimental research aims to evaluate its efficiency in improving students' vocabulary acquisition at SMPN 8 Rupat. Specifically, this study answers the research question of how effective the mnemonic strategy is in improving students' vocabulary acquisition abilities. This study used a one-group pretest-posttest methodology. A total of 19 students from class VIII A were selected as samples using cluster sampling. Based on the results, the mean score of the pre-test was 57.68, while the mean score of the post-test was 89.31. For more details, a paired T-test was conducted on the students' pre-test and post-test scores. The results showed that the mnemonic strategy can improve students' vocabulary mastery at SMPN 8 Rupat because researchers used t-test analysis at the significance level (p) = 0.05 with degrees of freedom (df) = N-1, where N = the number of subjects (19 students) and the t-table value is 2.101. t-test statistics and analysis for independent samples are applied. From the above calculation, it can be seen that the t-count value of adjectives and nouns is greater than the t-table value (4.73>2.101). This means that there is a significant difference between students' vocabulary before and after using the mnemonic strategy on the vocabulary of class VIII students in SMPN 8 Rupat.